Synthesis and Characterization of Bioplastic from Macroalgae Padina australis - Putri, Lily Surayya Eka; Saridewi, Nanda; Farah, Sabrina (Jurnal Kimia Valensi, 2023)
Synthetic plastics are one of the more significant contributors to waste in the environment. Bioplastic is a type of plastic that is environmentally friendly because it is made from biomass. In this study. brown macroalgae. Padina australis. is one of the potential raw materials found in large quantities in Indonesian waters and used to produce bioplastics with filtration technique. The aim of this study was to synthesis bioplastics using P. australis alginate with glycerol plasticizer.The alginate macroalgae were mixed with glycerol as a plasticizer in the following proportions: 1:15. 1:25. 2:15. and 2:25. with the quality determined through tensile strength measurements. water solubility. and degradation time. On day 12. the tensile strength of P. australis bioplastic was 3.24-7.33 MPa. the water solubility was 61.79-65.19%. and the biodegradability rate was 0.1-20.0%. When the macroalgae alginate and glycerol formulation was 2:25. the best bioplastic film produced had a tensile strength of 7.33 MPa and a water solubility of 61.79%. which was lower than the Indonesia National Standard number 7818/2016 for bioplastic products. P. australis. however. has the potential to be a promising alternative bioplastic product that contributes to the reduction of petroleum-based plastic pollution in the environment. Furthermore. as a preliminary study. it will be improved to meet industrial standards or find the products that match these characteristics.